Correlation of Serum Bile Acids with Liver Enzymes and Perinatal and Maternal Outcome in Cholestasis in Pregnancy - Kaur, Satinder; Huria, Anju; Kaur, Jasbinder; Kumar, Pradip (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v5i1.5058 NJOG 2010 Jul-Aug; 5(1): 32-36